2016
DOI: 10.1155/2016/8212459
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chronic Obstructive Pulmonary Disease on Long-Term Outcome in Patients with Coronary Artery Disease Undergoing Percutaneous Coronary Intervention

Abstract: Objective. The aim of this study was to investigate the association between COPD and major adverse cardiovascular and cerebral events (MACCE) in patients undergoing percutaneous coronary intervention (PCI). Methods. 2,362 patients who underwent PCI were included in this study. Subjects were divided into 2 groups: with COPD (n = 233) and without COPD (n = 2,129). Cox proportional hazards models were analyzed to determine the effect of COPD on the incidence of MACCE. Results. The patients with COPD were older (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 30 publications
1
9
1
Order By: Relevance
“…34 COPD patients from this research were more exposed to tobacco, but the relationship between COPD and CAD was found even in ex-smokers, since after COPD develops, cessation of smoking may not completely attenuate the inflammatory process. 34 According to Zhang et al, 35 inflammatory changes in lung vessel structure and function result in increased arterial stiffness independent of exposure to cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…34 COPD patients from this research were more exposed to tobacco, but the relationship between COPD and CAD was found even in ex-smokers, since after COPD develops, cessation of smoking may not completely attenuate the inflammatory process. 34 According to Zhang et al, 35 inflammatory changes in lung vessel structure and function result in increased arterial stiffness independent of exposure to cigarette smoke.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, we revealed a higher rate of periprocedural CAs, MIs and no-reflows in patients from the COPD group. The study published by Zhang et al demonstrated an increased rate of in-hospital MIs in patients with rather than without COPD (16.3% vs. 4.6%) [ 14 ]. The study was conducted among a group of 2,362 patients undergoing PCI.…”
Section: Discussionmentioning
confidence: 99%
“…The important fact is that the authors did not mention any information about the distribution of CAD clinical presentation before PCI or the type of coronary atherosclerosis. Nevertheless, they also showed that the incidence of heart failure was greater in the COPD group as compared to the non-COPD group (22% vs. 9.2%) [ 14 ]. The increased rate of periprocedural MIs in patients with COPD as compared to the non-COPD group could be explained by more complex and disseminated coronary atherosclerosis as well as the difference in clinical presentation resulting from it.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of COPD and CAD is detrimental and associated with a negative impact on the outcome of the affected individuals. Patients with undiagnosed COPD who undergo PCI have higher morbidity and mortality, 12 , 13 and cardiovascular comorbidity increases the burden of patients with COPD as more than a quarter of patients with COPD die of cardiovascular disease. 14 , 30 Moreover, patients admitted for COPD exacerbation were found to have a high troponin level in the absence of acute coronary symptoms and a subsequent coronary angiography showed significant coronary stenosis.…”
Section: Discussionmentioning
confidence: 99%
“… 8 Although the prevalence of COPD in patients with CAD is not widely reported, available reports show that it ranges from 10.5% to 33.6% and most cases of COPD were not previously diagnosed. 9 12 Lastly, patients with CAD who have coexisting COPD have increased morbidity and mortality, 12 , 13 whereas cardiovascular disease comorbidity is an important cause of mortality in patients with COPD. 14 …”
Section: Introductionmentioning
confidence: 99%